The Mind of a killer case study of a murderer - Wagner, Betsy; Reiss, Peter; Discovery Channel (Firm); ABC News; Films For The Humanities & Sciences (Firm) (Princeton, N. J : Films for the Humanities & Sciences, 2005)
An exclusive interview with serial killer Joel Rifkin, convicted of strangling 17 women, is combined with neurological testing, brain scans, and even information derived from laboratory studies of animal aggression to attempt to shed light on Rifkin's obscure motivation to kill - a motivation tha is a mystery even to himself
Producers, Betsy Wagner, Peter Reiss ; editor, Bernie Jellig
Keywords: Rifkin, Joel, -- 1959-; Murderers -- Psychology; Violence -- Research; Homicide -- psychology; Criminal psychology; Brain -- Research